Distribution Channel and Prices as Critical Factors for Sales Volume Improvement - Lili Suryati; Lusiah Lusiah (DINASTI RESEARCH, 2022)
This study aims to examine the effect of Distribution Channel and Price on Sales Volume Improvement. This study uses explanatory quantitative research on 20 star hotelin Jakarta with 80 respondents processed using the SEM-PLS approach. The results of the study indicate that Distribution Channel directly influences Sales Volume ImprovementStar Hotel in Jakarta and Price directly influence Sales Volume ImprovementStar Hotel in Jakarta.